سياسات عامة وتنظيمات ادارية - مصباحي, علاء الدين (جامعة الوادي university el-oued)
تحاول هذه الدراسة تسليط الضوء على واقع سياسة التأمين الصحي في الجزائر بصفة عامة وعلى واقع خدمات التأمين الصحي على مستوى صندوق التأمينات الاجتماعية للعمال الأجراء لوكالة الوادي بصفة خاصة، وهذا من خلال استعراض أهم السياسات المتعلقة بالتأمينات الاجتماعية في إطار عصرنة منظومة الضمان الاجتماعي، ومدى فعالية هذه السياسات على المؤمن لدى صندوق الضمان الاجتماعي. وقد تعرضت الدراسة بداية إلى السياق العام لسياسة التأمين الصحي في الجزائر من خلال استعراض الأطر القانونية والتنظيمية للتأمين الصحي في الجزائر، وواقع التامين الصحي في الصندوق الوطني للضمان الاجتماعي بالجزائر وسياسات وبرامج تحسين خدمات التأمين الصحي، وتعرضت الدراسة في جزئها التطبيقي الى سياسة التأمين الصحي في بعض المؤسسات العمومية المنطوية ضمن الصندوق الوطني للتأمينات الاجتماعية للعمال الأجراء لولاية الوادي من خلال استعراض عموميات حول وكالة الصندوق الوطني للتأمينات الاجتماعية للعمال الأجراء في ولاية الوادي، وإبراز واقع خدمات التأمين الصحي في بعض المؤسسات العمومية ضمن الصندوق، وقد استنتجت الدراسة أنه لابد من التأكيد علـى مسـاهمة سياسات وبـرامج التـأمین الصـحي فـي تخفيف العبء على المؤمن، مـن خـلال تـوفیر الحمایة الاجتماعية ضد خطر المرض وتقديم خدمات تأمين صحي تحقق رضا المؤمن.This study attempts to shed light on the reality of health insurance policy in Algeria in general and on the reality of health insurance services at the level of the Social Insurance Fund for wage-workers of the Valley Agency in particular, and this by reviewing the most important policies related to social insurance within the framework of the modernization of the social security system, and the effectiveness of these policies. Policies on the insured at the Social Security Fund. The study was initially exposed to the general context of health insurance policy in Algeria by reviewing the legal and regulatory frameworks for health insurance in Algeria, the reality of health insurance in the National Social Security Fund in Algeria and policies and programs for improving health insurance services. Public institutions involved within the National Fund for Social Insurance for Salaried Workers of El-Oued State by reviewing the generalities about the agency of the National Fund for Social Insurance for wage-workers in El-Oued, and highlighting the reality of health insurance services in some public institutions within the Fund. The study concluded that it is necessary to emphasize the contribution of health insurance policies and health insurance programs reduce the burden on the insured, by providing social protection against the risk of disease and providing health insurance services that achieve the insurer’s satisfaction.
م.س.ع.21
Keywords: التأمين الصحي، التأمينات الاجتماعية، الحمایة الاجتماعية; health insurance, social insurance, social protection